HUBUNGAN PENDIDIKAN DAN PEMBANGUNAN NASIONAL DENGAN KEBIJAKAN DAN PERENCANAAN - Aprilliantoni, Aprilliantoni; Wahyuni, Sri; Iqbal, Muhammad (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study discusses the relationship between education and national development in Indonesia, focusing on the policies and planning priorities undertaken by the government. In this context, education serves not only as a means of knowledge transfer but also as a key driver of social and economic development. The research aims to identify educational policy priorities to support national development, as well as the challenges faced and their implementation. The study examines the relationship between education and national development, emphasizing policy and planning priorities. Character education and improving education quality are the main programs of the development policy. Through synergy between the government and educational institutions, it is expected that an education system aligned with global challenges can be established. This research also analyzes education planning strategies that align with the development vision. The study employs a descriptive and relational learning approach to explore the relationship between education and national development in Indonesia with the quality of education. Data will be analyzed using descriptive statistics and correlation analysis. The findings reveal that government policies and planning priorities have a significant impact on the quality of education, positively influencing education quality and improving learning outcomes, creating a better learning environment for students. Based on the research results, it is concluded that government policies and planning priorities are important factors that can influence the quality of education. Therefore, further research is needed to improve education quality. We believe this study can provide detailed information on education and national development in Indonesia, with an emphasis on the policies and planning priorities taken by the government at the national level to achieve sustainable education goals.